Hechicería, cultura folclórica y justicia capitular. El proceso de Tuama (Santiago del Estero), 1761 - Judith Faberman (Instituto de Investigaciones en Ciencias Sociales y Humanidades, 2000)
Based on a sorcery criminal process this article analyses both acculturation and strategies of resistance fostered in Indian settlements of Santiago del Estero. Focused mostly on the salamanca, a ritual that in some of its features evokes the European sabbat, the author proposes that the salamancas are an exponent of the hybrid culture that emerged in the area during the colonial time.